2022
DOI: 10.3390/cancers14030785
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenia and Immediate Complications and Mortality in Patients with Oral Cavity Squamous Cell Carcinoma Undergoing Surgery

Abstract: Sarcopenia negatively affects oncologic outcomes. However, studies have yet to reveal whether it is associated with postoperative complications and survival among patients with oral cavity squamous cell carcinoma (OSCC). This study retrospectively enrolled 592 patients undergoing primary OSCC surgery with available computed tomography (CT) images of their third cervical vertebrae (C3) within 30 days before surgery between January 2011 and December 2020. Preoperative sarcopenia, nutritional and frailty status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…In our study, the SCI-E database was used to obtain information on publications on the relationship between The relationship between sarcopenia and surgery was still a concern and discussed topic in recent years due to the significant roles played by sarcopenia in surgical procedures, as well as the prognosis after surgeries (24,25). A study that enrolled 480 older patients with gastrointestinal and hepatobiliary pancreatic tumors showed that patients with poor muscle strength may have poor outcomes after their first resection surgeries (26).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the SCI-E database was used to obtain information on publications on the relationship between The relationship between sarcopenia and surgery was still a concern and discussed topic in recent years due to the significant roles played by sarcopenia in surgical procedures, as well as the prognosis after surgeries (24,25). A study that enrolled 480 older patients with gastrointestinal and hepatobiliary pancreatic tumors showed that patients with poor muscle strength may have poor outcomes after their first resection surgeries (26).…”
Section: Discussionmentioning
confidence: 99%
“…High SII levels have been reported to be associated with postoperative complications of oral cavity squamous cell carcinoma and ovarian peritoneal carcinomatosis. 21,22 Xie et al 23 first discovered that the combination of tumor markers and SII was a significant predictor of postoperative complications for patients after colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…High SII levels have been reported to be associated with postoperative complications of oral cavity squamous cell carcinoma and ovarian peritoneal carcinomatosis. 21 , 22 Xie et al 23 first discovered that the combination of tumor markers and SII was a significant predictor of postoperative complications for patients after colorectal surgery. Based on the research by Xie, 23 this study further demonstrated that patients with the cutoff value of SII > 916.99 were more proven to have symptomatic AL than those without.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher SII was reported as a distinct prognostic indicator of OSCC in certain articles ( 19 , 26 , 28 ). In contrast, some researchers indicated the absence of any obvious association of SII with survival outcomes in OSCC ( 23 25 ). Consequently, to identify the precise impact of SII on predicting OSCC prognosis, this work carried out comprehensive literature retrieval for meta-analysis.…”
Section: Introductionmentioning
confidence: 95%